Determination of methionine requirement for Pekin ducks: an integrated linear broken line and quadratic polynomial regression approach - Wu, Yongbao; Cao, Junting; Tang, Jing; Yang, Yiwen; Hou, Shuisheng; Wen, Zhiguo (Frontiers in Animal Science, 2026)
This study evaluated the effects of dietary methionine (Met) levels on the growth performance of Pekin ducks and estimated their Met requirements during the starter (1 to 14 days; Exp. 1) and grower (15 to 35 days; Exp. 2) phases. In Exp. 1, 288 one-day-old male ducklings were randomly assigned to six diets containing analyzed Met levels of 0.291%, 0.343%, 0.392%, 0.438%, 0.483%, and 0.521% (six replicates; eight birds each). In Exp. 2, 150 ducks at 15 days of age were allocated to five diets with analyzed Met levels of 0.271%, 0.342%, 0.421%, 0.501%, and 0.566% (six replicates; five birds each). Growth performance was recorded in both experiments, and Met requirements were estimated using linear broken-line and quadratic polynomial models. During the starter phase, increasing Met intake resulted in linear and quadratic improvements in weight gain and a linear reduction in feed/gain (F/G). For the grower phase, weight gain showed a quadratic response, with the highest gain at 0.421% Met, while F/G decreased linearly and quadratically. Estimated Met requirements for the starter phase were 0.404% (linear broken-line) and 0.532% (quadratic polynomial), and for the grower phase were 0.371% and 0.473%, respectively. Using the intercept of the two models, recommended Met levels were 0.455% for starter ducks and 0.411% for growing ducks. These integrative values likely provide more practical and economically relevant recommendations than relying on a single model, as broken-line analysis may underestimate and quadratic models may overestimate actual nutrient requirements.